2016
DOI: 10.4236/ojneph.2016.62007
|View full text |Cite
|
Sign up to set email alerts
|

Taurolock Effectively Reduces Tunneled Dialysis Catheter-Related Infection and Catheter Exchange Rates among Hemodialysis Patients

Abstract: Aims: Catheter-related infection, which is one of the major side effects of the use of dialysis catheters, leads to increases in hospitalization, morbidity and mortality. Antibiotic lock is an option for reducing the incidence of these infections, but there are concerns regarding antibiotic resistance. A prior study demonstrated that Taurolock (a taurolidine lock) may reduce the rate of catheter-related infection. Methods and Material: This investigation was a prospective before-and-after study. During period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In our study, using Taurolock had a significantly lower incidence of catheter occlusion and longer duration of catheter function compared to the heparin lock. These findings are similar to the results of previous studies [17][18][19][20]. Heparin lock and Taurolock were not associated with clinical coagulopathy.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, using Taurolock had a significantly lower incidence of catheter occlusion and longer duration of catheter function compared to the heparin lock. These findings are similar to the results of previous studies [17][18][19][20]. Heparin lock and Taurolock were not associated with clinical coagulopathy.…”
Section: Discussionsupporting
confidence: 92%
“…7 We also found that our patients had a lower rate of interventions to maintain HD compared to the literature for in-centre HD for both TDC (0.4 vs 0.45) and AVF/AVG patients (0.32 vs 0.44). 8 Overall, our cohort of patients had a lower rate of hospital admission rates compared to the literature from EURODoPPs (0.33 vs 0.99) for all types of dialysis patients. 9 This is likely to be due to the selective nature of home HD, whereby the fittest patients are usually the ones well enough to be considered for it.…”
Section: Discussionmentioning
confidence: 52%